2018
DOI: 10.1002/ptr.6158
|View full text |Cite
|
Sign up to set email alerts
|

Curcumol induces cell cycle arrest and apoptosis by inhibiting IGF‐1R/PI3K/Akt signaling pathway in human nasopharyngeal carcinoma CNE‐2 cells

Abstract: Curcumol has been proved to possess antitumor effects in vivo and in vitro in several cancers. Previously, we have found that curcumol induced apoptosis in CNE-2 cells, but its underlying mechanism has not yet been studied well. Recently, our team clarified that curcumol inhibited colorectal cancer cells' growth partially through insulin-like growth factor 1 receptor (IGF-1R) pathway. Given the key importance of IGF-1R pathway in tumorigenesis, we want to explore whether curcumol effects on nasopharyngeal carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Cyclins D1 and E are important regulators of cyclindependent kinases that are involved in controlling the G0/G1 checkpoint and proliferation of cancer cells. Some anticancer drugs induce G0/G1 arrest by decreasing the levels of cyclins D1 and E. 30,31 Our results revealed that A549 cells treated with SCU underwent G0/G1 arrest, which was mainly the result of the downregulation of cyclin D1 and E expression.…”
Section: Discussionmentioning
confidence: 68%
“…Cyclins D1 and E are important regulators of cyclindependent kinases that are involved in controlling the G0/G1 checkpoint and proliferation of cancer cells. Some anticancer drugs induce G0/G1 arrest by decreasing the levels of cyclins D1 and E. 30,31 Our results revealed that A549 cells treated with SCU underwent G0/G1 arrest, which was mainly the result of the downregulation of cyclin D1 and E expression.…”
Section: Discussionmentioning
confidence: 68%
“…74 Studies have shown that oxidative stress and 75 Antioxidant therapy can increase the expression of medullary HIF in diabetic kidneys and improve renal oxidative damage. 76 HIF activation can attenuate changes in renal oxygen metabolism and mitochondrial function caused by diabetes, thereby reducing proteinuria and improving renal tubular interstitial damage. 77 The PI3K-Akt signaling pathway plays an important role maintaining insulin stability.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumol has been known to arrest the cell cycle at both G2/M and G0/G1 in several cancerous cells such as lung [52], breast [53], gastric [23], nasopharyngeal [63], and liver carcinomas [55]. In A549 and H1299 carcinoma cells, combinatorial treatment of celecoxib with curcumol lead to the accumulation of cells at G0/G1 phase while population of cells in S phase was found to be dropped after the treatment.…”
Section: Curcumol and Cell Cycle Arrestmentioning
confidence: 99%
“…SPC-A-1, TE-1, and AGS cells displayed substantial G0/G1 arrest while TE-1, AGS, and MGC-803 exhibited G2/M arrest followed by the treatment of curcumol [23,32,65]. Curcumol significantly prohibited growth of CNE-2 cells and caused cell cycle arresting at G0/G1 phase via increasing the expression of p21 and p27 while reducing the expression of CDKs and cyclins in a dose-dependent mode [63]. Curcumol treatment lead HepG2 cells towards G1 phase arrest mediated by mechanism activating pRB and p53 pathways which ultimately resulted in decreased cyclin A1 levels while enhanced mRNA expression level of p27KIP1, cyclin D1, CDK2, and CDK8 [55] (Table 2).…”
Section: Curcumol and Cell Cycle Arrestmentioning
confidence: 99%